Appointment scheduling of diagnostic facilities subject to non-stationary emergency demand and waiting time targets - Jing Wen; Na Geng; Xiaolan Xie (2016 IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA), 2016)
Diagnostic facility is one of the most important critical resources in the hospital. Patient scheduling plays an important role in managing these facilities, especially when they are shared between regular and emergency patients. Due to the non-stationary emergency arrival and waiting time targets of emergency patients, it is challenging for hospital managers to make appointment scheduling decision and real time scheduling decisions, i.e., how many regular patients could reserve the service and how to coordinate the service of both types of patients. To deal with this problem, this paper proposes a stochastic integer programming model by considering the uncertainty of emergency patients and their waiting time requirement. The objective is to minimize the weighted idle time, overtime, and patients' waiting time. Monte Carlo optimization is used to solve this model. Numerical experiments are proposed to show the usefulness of the proposed model for investigation of the influence of different parameters.